Current velocity, water quality, and benthic taxa as predictors for coral recruitment rates on the Great Barrier Reef - Matilde A. Drake; Sam H. C. Noonan; Mariana Alvarez-Noriega; Ahmad R. Rashid; Katharina E. Fabricius (PLoS ONE, 2025)
Coral reefs worldwide are experiencing frequent disturbances, rendering coral recruitment critical for population recovery. This large-scale study identifies environmental, spatial, and biotic drivers of coral recruit densities at 141 stations stratified across seven regions and three depths (1, 5, and 15 m depths) with contrasting environmental conditions across and along the Great Barrier Reef and the Torres Strait. Settlement tiles were deployed for two years, with coral densities and benthic cover quantified following retrieval. Benthic communities were assessed from tile images using the point-classification AI program ReefCloud. Environmental data were derived from in situ readings and environmental models. Across all sites, coral recruit densities averaged 187 ±  12 m‒2 (SE), with region-wide averages ranging from 43.5 ±  12 m‒2 to 247 ±  32 m‒2. Mean densities were 3-fold higher in the four clear-water regions compared to the three turbid-water regions. Boosted regression tree analyses showed that densities declined with increasing current velocity, sedimentation, and depth, and increased with increasing pH. From lowest to highest observed levels of current velocity, recruit densities declined by ~ 530 m‒2. From lowest to highest sedimentation, densities declined by ~ 300 recruits m‒2. Even relatively minor increases in sediment deposits from 0.1 to 38 mg cm‒2 were associated with a monotonic decline of ~ 130 recruits m‒2. Recruit densities were also weakly positively related to the cover of turf and crustose coralline algae on tile tops, and negatively related to fleshy invertebrate cover on the tile undersides. Some variation in the cover of these benthic taxa was also related to environmental conditions (e.g., sedimentation and currents), suggesting the possibility of additional indirect environmental effects on recruit densities. Our results highlight the strong role of current velocity and water quality as regulators of coral recruitment success, likely influencing the capacity of reef sites to recover after a disturbance.